British gods religion in modern Britain - Bruce, Steve 1954- (Oxford, United Kingdom Oxford University Press, 2020)
The big picture is well-known: over the last century, religion in Britain has lost power, popularity, and plausibility. Here, Steve Bruce charts the quantifiable changes in religious interest and observance over the last fifty years by returning to a number of towns and villages that were the subject of detailed community studies in the 1950s and 1960s, to see how the status and nature of religion has changed. Drawing on both detailed data on baptism rates, church weddings, church attendance and the like, and on his extensive fieldwork, he considers the broader picture of religion today: the status of the clergy, the churches' attempts to find new roles, links between religion and violence, and the impact of the charismatic movement.0Along the way, Bruce encounters and engages with the contemporary rise of secularism, considering our everyday secular tensions with religion: arguments over moral issues such as abortion and gay rights, the effect of social class on belief, the impact of religion on British politics, and the ways that local social structures strengthen or weaken religion. Analysing the obstacles to any religious revival, he explores how the current stock of religious knowledge is so depleted, religion so0unpopular, and committed believers so scarce that any significant reversal of religion's decline in Britain is unlikely
Keywords: Religion and sociology -- Great Britain -- History -- 20th century; Secularism -- Great Britain -- History -- 20th century; Secularism -- Great Britain -- History -- 21st century; Religion; Religion and sociology; Secularism; History; Great Britain -- Religion -- 20th century; Great Britain -- Religion -- 21st century; Great Britain